2019
DOI: 10.1029/2019gl084534
|View full text |Cite
|
Sign up to set email alerts
|

Wildfire Impact on Environmental Thermodynamics and Severe Convective Storms

Abstract: Wildfires are extreme events associated with weather, climate, and environment and have been increasing globally in frequency, burn season length, and burned area. It is of great interest to understand the impacts of wildfires on severe convective storms through releasing heat and aerosols into the atmosphere. We have developed a model capability that can account for the impact of sensible heat fluxes from wildfires on thermodynamics and is computationally efficient. The pyrocumulonimbus clouds associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 48 publications
4
25
0
Order By: Relevance
“…These processes appear to be more effective for weak convections than deep convections and were in fact well simulated in the former cases. The results are also consistent with some previous observationbased studies (Jiang et al, 2018;Zhao et al, 2018). and Zhao et al (2018) both concluded that an increase in fire aerosols generally reduces cloud optical thick-ness of deep convection, while Zhao et al (2018) further showed that fire aerosols tend to invigorate weak convection for small-to-moderate aerosol loading.…”
Section: Casesupporting
confidence: 92%
“…These processes appear to be more effective for weak convections than deep convections and were in fact well simulated in the former cases. The results are also consistent with some previous observationbased studies (Jiang et al, 2018;Zhao et al, 2018). and Zhao et al (2018) both concluded that an increase in fire aerosols generally reduces cloud optical thick-ness of deep convection, while Zhao et al (2018) further showed that fire aerosols tend to invigorate weak convection for small-to-moderate aerosol loading.…”
Section: Casesupporting
confidence: 92%
“…Similar effects of forest fires on convective processes were reported in other studies [82][83][84]. Zhang et al [84] used a modified WRF-Chem model to show that both heat and aerosol effects increase low-level temperatures and mid-level buoyancy and enhance consequently the convective intensity. Such effects in our study manifested in changes of the CAPE and CIN indices.…”
Section: Discussionsupporting
confidence: 54%
“…It is likely that a combination of the variability in the magnitude, location, and season of the fires plus synoptic variability contributes to the decreased correlation and statistical significance between the domain mean MERRA‐2 and NIFC data sets. Hence, the increasing trend in fire burn acreage and the atmospheric contribution of carbonaceous aerosols with respect to synoptic forcing should continue to be investigated in future research efforts involving aerosol‐cloud‐climate interactions (Zhang et al, 2019). In addition, air quality concerns typically increase in areas downwind of fire activity which also warrant further investigation (Brey et al, 2018; Chin et al, 2014; Hand et al, 2013; Malm et al, 2017; Miller et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Aerosols contribute to cloud development due to their inherent ability to activate as cloud condensation nuclei (CCN) under favorable dynamic and thermodynamic conditions (Fan et al, 2015(Fan et al, , 2016Liu & Li, 2014;Logan et al, 2014Logan et al, , 2018Rosenfeld et al, 2008;Zhang et al, 2019). Rising motion resulting from synoptic and mesoscale dynamics along with sufficient moisture is needed for CCN to undergo net condensational growth to become cloud droplets that can eventually become raindrops via the collision/coalescence process (Liu & Li, 2014;Pruppacher & Klett, 1997;Rosenfeld et al, 2008).…”
Section: Introductionmentioning
confidence: 99%